DAMPAK LINGKUNGAN KERJA PADA PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION DENGAN PENDEKATAN MODERATED REGRESSION ANALYSIS - Dunggio, Maryam; Soraya, Elly; Nurali, Elma Fitria (Kinerja, 2023)
This study aims to analyze the effect of work stress on turnover intention and analyze the role of the work environment in moderating the effect of work stress on turnover intention. The research was conducted on employees of PT. Emblem Asia with a sample of 73 respondents. Data analysis was carried out using a moderated regression analysis method with a Moderated Regression Analysis (MRA) approach. The results of this study prove that work stress has a positive and significant effect on turnover intention. Meanwhile, the work environment can act as a quasi-moderator variable. The work environment can affect turnover intention but can also interact with work stress to strengthen/weaken the effect of work stress on turnover intention.